A high power X‐band internally‐matched power amplifier with 705 W peak power and 51.7% PAE. Issue 12 (24th August 2021) - Gu, Liming; Feng, Wenjie; Zhou, Sutong; Tang, Shijun; Wang, Shuai
Abstract: A high power and high efficiency fully internally‐matched GaN power amplifier operating at X ‐band is proposed. The device is realized by matching four GaN power bars of 18‐mm gate periphery. To reduce the size, single layer capacitors with high permittivity are used, and the impedance matching circuits are fabricated on Al2 O3 ceramic substrate. The device exhibits saturated output power of more than 660 W with power gain above 9.8 dB within the frequency range of 8.2–8.8 GHz, based on the pulse mode of 100 μs pulse width and 10% duty. In addition, the highest saturated output power and power added efficiency reach 705 W and 51.7% with packaging compact size (26 mm × 17.4 mm).